Encouragement Is Not Enough: Perceptions and Attitudes towards Corrective Feedback and Their Relationship to Self-Efficacy - Vasti Holstun; Neil Rigsbee; Lynn Bohecker (Teaching and Supervision in Counseling, 2021)
This correlational study explored the relationship between feedback and counselor self-efficacy during online counselor education residency. Participants (N=145) were students from eight Council for Accreditation of Counseling and Related Educational Programs (CACREP) accredited online counseling programs who completed instruments on perceptions of positive and corrective feedback, attitudes towards corrective feedback, and counselor self-efficacy. Results showed a significant positive correlation between perceptions of corrective feedback and self-efficacy. Two factors related to perceptions of corrective feedback also showed significant correlations with self-efficacy. Implications concerning providing corrective feedback in supervision for counselor in training are discussed.
Keywords: self-efficacy; corrective feedback; online counselor education; counselor supervision; correlational research